Fabrication of alternating layers of multimaterial ceramics with bioinspired microstructures - Chang, Gwendolyn Yu Qian (Nanyang Technological University, 2024)
Ceramics are known for their high strength, stiffness, and hardness. However, they usually show poor toughness, which limits their use in applications that need to withstand damage. Previous studies have shown that bioinspired designs, such as the nacre-inspired layered arrangement of hard and soft layers (inspired by nacre in abalone shell), can help mitigate poor toughness. In particular, a layered arrangement to combine alumina and zirconia as hard and soft layer, respectively, could be interesting for structural, transport, energy absorption, biomedical applications, etc. However, the precise microstructural control and the interpenetrating distribution of alumina and zirconia is challenging.